Synthesis, characterization, antitumoral and osteogenic activities of quercetin vanadyl(IV) complexes - Ferrer, Evelina Gloria (2006)
The development of new vanadium derivatives with organic ligands, which improve the beneficial actions (insulin-mimetic, antitumoral) and decrease the toxic effects, is of great interest. A good candidate for the generation of a new vanadium compound is the flavonoid quercetin because of its own anticarcinogenic effect. The complex [VO(Quer)2EtOH]; n; (QuerVO) has been synthesized and characterized by means of different spectroscopic techniques (UV–vis, Fourier transform IR, electron paramagnetic resonance) and its magnetic and stability properties. The inhibitory effect on bovine alkaline phosphatase (ALP) activity has been tested for the free ligand, the complex as well as for the vanadyl(IV) (comparative purposes). The biological activity of the complex on the proliferation of two osteoblast-like cells in culture, a normal one (MC3T3E1) and a tumoral one (UMR106), has been compared with that of the vanadyl(IV) cation and quercetin. The differentiation osteoblast markers ALP specific activity and collagen synthesis have been also tested. In addition, the effect of QuerVO on the activation of the extracellular regulated kinase (ERK) pathway is reported. The bone antitumoral effect of quercetin alone was established with the cell proliferation assays (it inhibits the proliferation of the tumoral cells and does not exert any effect on the normal osteoblasts). Moreover, the complex exerts osteogenic effects since it stimulates the type I collagen production and is a weak inhibitory agent upon ALP activity. Finally, QuerVO stimulated the ERK phosphorylation in a dose–response manner and this activation seems to be involved as one of the possible mechanisms for the biological effects of the complex.